Pemanfaatan Buah Nipah dan Buah Naga Merah dalam Pembuatan Fruit leather - Danang Apriyan Idi Nuegroho; Shanti Fitriani; Rahmayuni Rahmayuni (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
This study aims to get the best combination of nipa fruit and red dragon fruit. The research used a Complete Randomized Design (CRD) with four treatments and four replications. The treatment was the ratio of nipa fruit puree and red dragon fruit puree, namely: NM1 (100% and 0), NM2 (75% and 25%), NM3 (50% and 50%), and NM4 (25% and 75%). The data obtained were statistically analyzed using Anova and DNMRT at 5%. The research showed that ratio of nipa fruit puree and red dragon fruit puree showed significant effect on moisture, ash content, degree of acidity (pH), total crude fiber content, total sugar content and organoleptic tests. The best treatment of fruit leather from this research was NM4 which had moisture 12,67%, ash content 0,63%, degree of acidity (pH) 3,40, crude fiber content 2,15% and total sugar content 44,88%. The NM4 treatment had red color, a red dragon fruit flavour, sweet taste, springy texture and overall assesment of fruit leather was preferred by the panelists. Keywords:Fruit leather, nipa fruit, red dragon fruit